Cyclic Hexapeptide Mimics of the LEDGF Integrase Recognition Loop in Complex with HIV‐1 Integrase. (6th July 2018) - Northfield, Susan E.; Wielens, Jerome; Headey, Stephen J.; Williams‐Noonan, Billy J.; Mulcair, Mark; Scanlon, Martin J.; Parker, Michael W.; Thompson, Philip E.; Chalmers, David K.
Abstract: The p75 splice variant of lens epithelium‐derived growth factor (LEDGF) is a 75 kDa protein, which is recruited by the human immunodeficiency virus (HIV) to tether the pre‐integration complex to the host chromatin and promote integration of proviral DNA into the host genome. We designed a series of small cyclic peptides that are structural mimics of the LEDGF binding domain, which interact with integrase as potential binding inhibitors. Herein we present the X‐ray crystal structures, NMR studies, SPR analysis, and conformational studies of four cyclic peptides bound to the HIV‐1 integrase core domain. Although the X‐ray studies show that the peptides closely mimic the LEDGF binding loop, the measured affinities of the peptides are in the low millimolar range. Computational analysis using conformational searching and free energy calculations suggest that the low affinity of the peptides is due to mismatch between the low‐energy solution and bound conformations. Abstract : Structural troubleshooting : Cyclic peptides are shown by X‐ray crystallography to closely mimic the binding of the LEDGF loop to HIV integrase. However, these compounds have affinities in the millimolar range. Computational modelling suggests that although the peptides can conform to their protein binding site, their conformation in solution differs substantially from the bound conformation, imparting an entropic cost to binding.